El culto a San Isidoro. Reliquias e imágenes. Iconografía sevillana - Sanz Serrano, María Jesús (Estudios humanísticos. Geografía, historia y arte, 1999)
The main object of this paper is to study the way that Saint Isidore has been figured over the past centuries. Relics and reliquaries, as well as sculptures and pictures from León and Seville are studied in this research work.